2020
DOI: 10.21037/apm.2020.03.18
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the advanced lung cancer inflammation index in early-stage non-small cell lung cancer patients undergoing video-assisted thoracoscopic pulmonary resection

Abstract: Background: The aim of this study was to assess the prognostic value of the preoperative advanced lung cancer inflammation index (ALI) in early stage non-small lung cancer (NSCLC) patients who received videoassisted thoracoscopic surgery (VATS) pulmonary surgery as their only therapy.Methods: We retrospectively reviewed the medical records of patients who were diagnosed with earlystage NSCLC and received a VATS pulmonary resection from January 2014 to June 2016 in the Department of Thoracic Surgery, West China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…8,9 ALI-related pulmonary edema and the resulting intrinsic inflammatory process are the leading mortality cause after thoracic surgery and significantly reduces the 1-year survival rate. 10 Dexmedetomidine (DEX) is a highly selective α 2 adrenergic receptor agonist with current clinical use. DEX has pulmonary protective benefits in lung injury cases through its effect on pulmonary vascular ischemia-reperfusion injury and inflammatory cytokine release.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 ALI-related pulmonary edema and the resulting intrinsic inflammatory process are the leading mortality cause after thoracic surgery and significantly reduces the 1-year survival rate. 10 Dexmedetomidine (DEX) is a highly selective α 2 adrenergic receptor agonist with current clinical use. DEX has pulmonary protective benefits in lung injury cases through its effect on pulmonary vascular ischemia-reperfusion injury and inflammatory cytokine release.…”
Section: Introductionmentioning
confidence: 99%
“…Whether receiving targeted treatment [ 80 ], 1st line chemotherapy [ 81 ], radical surgery [ 82 , 83 ], or chemotherapy combined with targeted treatment [ 84 ], ALI shows prognostic value. Even in patients at the early stage of NSCLC, ALI also has a prognostic value [ 85 , 86 ]. In lung cancer patients with poor performance status, ALI has a more prominent prognostic value [ 87 , 88 ].…”
Section: Albumin-related Inflammation Markers Based On Peripheral Blo...mentioning
confidence: 99%
“…At present, the pathological mechanism of postoperative recurrence of NSCLC was still in the stage of exploration, and the medical community had conducted a lot of studies on the related factors of postoperative recurrence of NSCLC. ese ndings suggested that postoperative chemoradiotherapy, tumor di erentiation degree, tumor diameter, TNM stage, number of lymph node metastasis, and mediastinal lymph node metastasis were related to the recurrence of NSCLC after radical resection [3][4][5]. However, there were few reports on the risk of recurrence and the nomogram model after radical NSCLC surgery, and there was still a lack of a simple, rapid, and e ective method to predict recurrence after radical NSCLC surgery.…”
Section: Introductionmentioning
confidence: 99%